2012
DOI: 10.1589/jpts.24.1127
|View full text |Cite
|
Sign up to set email alerts
|

Stretching Versus Mechanical Traction of the Spine in Treatment of Idiopathic Scoliosis

Abstract: Abstract.[Purpose] Traction-based therapies are non-invasive and probably cost-effective and have received interest recently. This study was conducted to compare two training programs, traction and stretching exercises, in rehabilitation of moderate scoliotic patients.[Subjects] Forty patients who were 15 to 25 years of age and had moderate scoliosis (Cobb's angle of 20 to 40 degrees) were randomized to either a stretching exercises group (n=20) or mechanical traction group (n=20).[Methods] All the patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…Therefore, the stretching exercises implemented in the first stage may have relaxed the muscles that were asymmetrically shortened around the spine and lengthened the trunk, thereby increasing flexibility. Zakaria et al 10 ) showed that stretching exercises decreased muscle spasms on the concave side and hyperactivity and corrected the curvature of the lumbar region by lengthening the shortened muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the stretching exercises implemented in the first stage may have relaxed the muscles that were asymmetrically shortened around the spine and lengthened the trunk, thereby increasing flexibility. Zakaria et al 10 ) showed that stretching exercises decreased muscle spasms on the concave side and hyperactivity and corrected the curvature of the lumbar region by lengthening the shortened muscles.…”
Section: Discussionmentioning
confidence: 99%
“…The strengthening exercises implemented in the final stage activated the muscles that were corrected using the Schroth exercises and may have helped the patient maintain spinal stability by strengthening the trunk muscles. Zakaria et al 10 ) reported that the use of strengthening exercises for the weakened muscles on the convex side corrected the body’s line of gravity and improved muscle balance.…”
Section: Discussionmentioning
confidence: 99%
“…Stretching exercises implemented in the first stage may have relaxed the muscles that were asymmetrically shortened around the spine and stretched the muscles around the trunk, increasing flexibility. Zakaria et al (2012) showed that stretching exercises reduced muscle spasms in the concave side and hyperactivity and corrected bending of the lumbar region extending shortened muscles.…”
Section: Resultsmentioning
confidence: 99%
“…Although these exercise methods have limitations in their ability to arrest and correct moderate or severe scoliosis, they are effective for mild scoliosis or when performed in conjunction with an orthosis or traction treatment 13 ) . There are many reports on the effectiveness of exercise therapies for scoliosis treatment 14 , 15 , 16 , 17 , 18 ) . However, until recently, scoliosis treatment was decided mainly on the basis of the level of deformation and speed of progression, with little or no regard to its effect on cardiopulmonary function.…”
Section: Introductionmentioning
confidence: 99%